PEKERJA ANAK DI SEKTOR INFORMAL PENCUCIAN MOBIL TENGGARONG - Jumaidi Nur (Center of Language and Cultural Studies, 2015)
Children labors in the Car Wash Units informal sector is particularly obtained in Tenggarong, the capital of Kutai Kartanegara county. This condition is beyond an expected condition that Free Children Labor Zone in Kutai Kartanegara is executed in Kutai Kartanegara. This paper reports an identification on Children Labors in Car Wash Units in Tenggarong, providing other facts that a struggle is remaining necessary to make the program successful.